Associations Between Physical Activity, Blood-Based Biomarkers of Neurodegeneration, and Cognition in Healthy Older Adults: The MAPT Study. (17th April 2021) - Raffin, Jérémy; Rolland, Yves; Aggarwal, Geetika; Nguyen, Andrew D; Morley, John E; Li, Yan; Bateman, Randall J; Vellas, Bruno; Barreto, Philipe de Souto; ,
Abstract: Physical activity (PA) demonstrated benefits on brain health, but its relationship with blood biomarkers of neurodegeneration remains poorly investigated. We explored the cross-sectional associations of PA with blood concentrations of neurofilament light chain (NFL) and beta amyloid (Aβ)42/40 . We further examined whether the interaction between PA and these biomarkers was longitudinally related to cognition. Four-hundred and sixty-five nondemented older adults engaged in an interventional study and who had a concomitant assessment of PA levels and blood measurements of NFL (pg/mL) and Aβ 42/40 were analyzed. A composite Z -score combining 4 cognitive tests was used for cognitive assessment up to a 4-year follow-up. Multiple linear regressions demonstrated that people achieving 500–999 and 2000+ MET-min/week of PA had lower (ln)NFL concentrations than their inactive peers. Logistic regressions revealed that achieving at least 90 MET-min/week of PA was associated with a lower probability of having high NFL concentrations (ie, ≥91.961 pg/mL [third quartile]). PA was not associated with (Aβ)42/40 . Mixed-model linear regressions demonstrated that the reverse relationship between PA and cognitive decline tended to be more pronounced as Aβ 42/40 increased, while it was dampened with increasing levels of (ln)NFL concentrations. This study demonstrates that PA is associated with blood NFL but not with Aβ 42/40 . Furthermore, it suggests that PA may attenuate the negative association between amyloid load and cognition, while having high NFL levels mitigates the favorable relationship between PA and cognition. More investigations on non demented older adults are required for further validation of the present findings.